Analysis of laboratory critical values at a referral Spanish tertiary university hospital - Arbiol-Roca, Ariadna (Array, 2018)
Introduction: The aim of this study was to analyse critical value data from our laboratory and compare our critical value reporting policy withothers in the literature.Materials and methods: Analysis of critical values was performed on data obtained over a 6-month period in a tertiary university hospital.Results: We identified 5723 critical values, of which approximately 80% came from STAT testing (4577), 15% from routine inpatients testing (884)and 5% from routine outpatients testing (262). The highest proportion of critical values corresponded to oxygen partial pressure (17.7%), followedby potassium ion (17.6%) concentrations. The parameters associated with the highest critical value notification percentage in emergency patientswere pH, haematocrit, glucose, potassium ion and haemoglobin concentrations. In inpatients, these parameters were glucose, phosphate, haemoglobin,sodium ion and potassium ion concentrations. In outpatients, they were calcium and potassium concentrations.Conclusions: The analysis of critical values in our hospital is in accordance with that reported in the literature. Our findings demonstrate the importanceof incorporating improvement actions not only in critical value notification, but especially in the registration of this activity.